Expression between Arabic and Semitic languages - Awad, Sami; Shreiki , Ahmed (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This paper deals with the link between Semitic and Arabic languages,that it showed the ancientness of the Arabic , and explained the concept of Semitic languages, and mentioned the most important views in their home country and their common characteristics. The research then presented the historical understanding of the Arab-Semitic relationship, confirming the interaction that emerged in the pre-Islamic era through interaction with the Bible, which was translated into Arabic Whether the Arabs are translators or were the people of these heavenly books; the result proves the principle of interaction between languages that these books were written with and the Arabic language, with the continuation of this interaction clearly in the era of the Prophet and his companions through various forms and ways. The research then discusses the phenomenon of expression, then the ancientness of the phenomenon of expression in Semitic languages in general, and Arabic in particular, through the presentation of the most important proof of authenticity in these languages, Although the Arabic is the most conservative. The research ended with conclusions and recommendations.